FREQUENCY NOISE INFLUENCE ON FUNCTIONING OF FREDKIN QUANTUM GATE - Gorskyi, Gennadiy P.; Deibuk, Vitaliy G. (International Journal of Computing, 2010)
The influence of detuning of radio frequency magnetic field (RFMF) on the functioning of nuclear magnetic resonance (NMR) quantum Fredkin gate is considered in this paper. It is shown that detuning of frequency decreases a probability of correct answer. If the spectral broadband of RFMF signal is increasing, then the main value of correct answer probability is decreasing too and standard deviation of this probability is increasing.